Auditoría tributaria a súper despensa Polita y su incidencia en la liquidación de impuestos ante el servicio de rentas internas. año 2017 - Fiallos Niza, Viviana Elizabeth (2018)
The present investigation related to the Tax Audit, to Súper Despensa Polita, a company located in the canton of Buena Fe, province of Los Ríos, with the purpose of providing relevant information and guiding the decisions that management must take. The examination is proceeded because it was evident that the tax processes applied at present, are deficient and do not satisfy the requirements demanded by the tax administration, the research addresses the following problem that was raised and is: How the Tax Audit a Super Pantry Polita affects the Liquidation of Taxes before the Internal Revenue Service. Year 2017? In this sense, the objective of the investigation is to evaluate the incidence of the Tax Audit in Super Polite Pantry in the Tax Settlement before the Internal Revenue Service. Year 2017, for which it was necessary to raise three specific objectives in order to meet the stated objective, which are: Identify the Internal Control processes in compliance with the tax obligations of Super Polite Pantry, in addition to determining the level of reliability, of the accounting information contrasted with the tax returns presented to the Internal Revenue Service and finalized with that of showing the deficiencies found in the execution for the determination of strategies in accounting practices. In the development of the research work, It uses information from both primary and secondary sources, that is, a qualitative research of documentary design and legal considerations pertinent to the area of taxation. With the results and observations of the audit, the businessmen will make decisions and place greater emphasis on the development of their management and overcoming their critical points detected.